2022
DOI: 10.1590/1806-9282.20220921
|View full text |Cite
|
Sign up to set email alerts
|

Thorax computed tomography findings and anti-SARS-CoV-2 immunoglobulin G levels in polymerase chain reaction-negative probable COVID-19 cases

Abstract: OBJECTIVE: This study aimed to evaluate the SARS-CoV-2 immunoglobulin G (IgG) levels after 6 months of polymerase chain reaction (PCR) negative but assumed to be COVID-19 positive cases to investigate the relationship between IgG levels and thoracic computed tomography (CT) findings. METHODS: This was a single-center study that included patients whose PCR test results were negative at least three times using nasopharyngeal swabs but had clinical findings of COVID-19 and thoracic CT findings compatible with vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In one study on 320 patients with confirmed COVID-19, the rate of chest computed tomography (CT) findings was significantly higher in patients with antibody positivity than in those with antibody negativity [88] . This was confirmed by another study showing that increasing severity of lung involvement is associated with high and persistent IgG antibody titers [89] . It is noteworthy that studies correlating more severe disease to more vigorous antibody response in COVID-19, are performed using laboratory tests, and not LFIAs, to assess the antibody titer [90] .…”
Section: Performance and Reliability Of Lfia In Post-infectionmentioning
confidence: 57%
See 1 more Smart Citation
“…In one study on 320 patients with confirmed COVID-19, the rate of chest computed tomography (CT) findings was significantly higher in patients with antibody positivity than in those with antibody negativity [88] . This was confirmed by another study showing that increasing severity of lung involvement is associated with high and persistent IgG antibody titers [89] . It is noteworthy that studies correlating more severe disease to more vigorous antibody response in COVID-19, are performed using laboratory tests, and not LFIAs, to assess the antibody titer [90] .…”
Section: Performance and Reliability Of Lfia In Post-infectionmentioning
confidence: 57%
“…Theoretically, LFIA should be superior to laboratory tests for large-scale evaluation of vaccine effectiveness due to lower costs and detection time [113] . However, although those LFIAs using the protein pair RBD/ACE2 can perform accurately for certain applications, in practice a number of problems have risen up in the use of rapid tests in post-vaccination [89] , [90] . No doubt that an association exists between the efficacy of the vaccine and neutralizing antibody titers, but comparison of immune responses provided by different vaccines is challenging and different approaches have been used by vaccines developers [117] , [118] .…”
Section: Lfia and Response To Vaccinationmentioning
confidence: 99%